Low-Dose Aspirin in Early Gestation for Prevention of Preeclampsia and Small-for-Gestational-Age Neonates: Meta-analysis of Large Randomized Trials - Roberge, Stéphanie; Sibai, Baha; McCaw-Binns, Affette; Bujold, Emmanuel (American Journal of Perinatology, 2016)
Objectives Meta-analyses of small to moderate size randomized controlled trials (RCTs) suggested that aspirin started before 17 weeks' gestation reduces the risk of preeclampsia and small-for-gestational-age (SGA) neonates. We evaluated data from large randomized trials originally excluded from meta-analyses.Methods We performed meta-analyses of RCTs including more than 350 participants that compared aspirin to placebo during pregnancy. Corresponding authors were contacted to obtain data according to gestational age. Outcomes included preeclampsia, severe preeclampsia, and SGA. Relative risks (RRs) with their 95% confidence intervals (CIs) were calculated.Results Data for women recruited before 17 weeks' gestation were obtained for three (50%) of the six eligible trials for a total of 11,949 participants including 3,293 recruited before 17 weeks' gestation with available data. We observed no impact of low-dose aspirin (60 mg) started before 17 weeks' gestation on the risk of preeclampsia (RR: 0.93; 95% CI: 0.75–1.15), severe preeclampsia (RR: 0.96; 95% CI: 0.71–1.28), or SGA (RR: 0.84; 95% CI: 0.56–1.26) and it was not statistically different than when started at or after 17 weeks' gestation.Conclusion Data from large randomized trials do not support greater benefits of low-dose aspirin (at 60 mg daily) when started before 17 weeks' gestation for the prevention of preeclampsia or SGA.
Keywords: pregnancy; aspirin; preeclampsia; fetal growth restriction; meta-analysis